Caracterização e infecção de células tronco mesenquimais e células semelhantes a neurônios, derivadas de cordão umbilical bovino pelo herpesvírus bovino Tipo 5 (BoHV-5) - Ferrari, Heitor Flávio [UNESP] (2013)
Bovine Herpesvirus type 5 (BoHV-5) infection results in non- suppurative meningoencephalitis which underlies significant economic losses in South America. Mesenchymal stem cells (MSCs) are found in fetal tissues, such as the umbilical cord. The goal of this research was to characterize the isolation and viability of bovine umbilical cord MSCs for in vitro differentiation into neuron-like cells (NLC) to be used as a model for experimental infection with BoHV-5. MSCs were isolated from Wharton's jelly and differentiated in vitro into adipogenic, chondrogenic, and osteogenic cells as well as NLC. The cells lines were characterized molecularly and immunophenotypically, using PCR, immunocytochemistry, and flow cytometry. The set of primers and panel of primary antibody used in the experiments confirmed the isolation of mesenchymal stem cells and their differentiation into neuronal-like cells. After adaptation and differentiation, the cells were infected with BoHV-5, exhibiting typical cytopathic effect and increased viral replication rate 72 h post-infection. Viral particles were identified in the NLC and in the extracellular environment. by in situ hybridization These results corroborate the use of MSCs as a source of NLC which can be used to study the pathogenesis of the experimental in vitro infection wtih BoHV-5